2023
DOI: 10.1155/2023/4964850
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Smoke Flavour in Wine from Chemical Composition of Smoke-Exposed Grapes and Wine

Abstract: Wine grapes exposed to smoke and wine made from grapes exposed to smoke can robustly be identified through their elevated concentrations of volatile phenols and phenolic glycosides serving as smoke markers, compared to concentrations typically found in non-smoke-exposed samples. Smoke-affected wines with high concentrations of volatile phenols and glycosides can have smoky flavours, but the relationship between concentrations of specific smoke markers in grapes and the intensity of smoky sensory attributes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Recently, a study that models the smoke taint flavor based on the VOC concentration in Australian grapes and wine using the Partial Least Squares approach for each variety with listing the VOCs that significantly contribute the smoke flavor is published. 31 Some VOCs, especially free guaiacol, significantly contribute to or are correlated with the smoke taint flavor in both studies; however, some VOCs are not, such as m-cresol. This study which includes the VOC concentration from more varieties of wine and grape samples in California and Oregon may allow us to discover how smoke taint affects the wine quality in different regions and varieties.…”
Section: ■ Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Recently, a study that models the smoke taint flavor based on the VOC concentration in Australian grapes and wine using the Partial Least Squares approach for each variety with listing the VOCs that significantly contribute the smoke flavor is published. 31 Some VOCs, especially free guaiacol, significantly contribute to or are correlated with the smoke taint flavor in both studies; however, some VOCs are not, such as m-cresol. This study which includes the VOC concentration from more varieties of wine and grape samples in California and Oregon may allow us to discover how smoke taint affects the wine quality in different regions and varieties.…”
Section: ■ Discussionmentioning
confidence: 83%
“…In this study, a complete data set that combines VOC concentrations of wine and grape samples from different varieties and smoke taint index is prepared, and it allows us to discover the VOC composition changes and the correlation between VOC concentrations and smoke taint index and to apply predictive modeling of the smoke taint index at the same time. Recently, a study that models the smoke taint flavor based on the VOC concentration in Australian grapes and wine using the Partial Least Squares approach for each variety with listing the VOCs that significantly contribute the smoke flavor is published . Some VOCs, especially free guaiacol, significantly contribute to or are correlated with the smoke taint flavor in both studies; however, some VOCs are not, such as m -cresol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rejection concentration of guaiacol is, however, much higher than the concentration observed in many "smoke-tainted" wines. 11 Hence, relying on guaiacol measures would likely result in a large number of false-negative classifications of wine samples as "fault-free", while, in fact, they can be recognized as smoke tainted when assessed by sensory evaluation. Similar to guaiacol, a number of other common wine flavor compounds are known that might be present in non-smoke-affected wines, such as volatile thiols PMT and 2-FMT and 4-ethyl phenol, and can confer characters that could be confused with smoke taint, such as "medicinal", "burnt rubber", "empyreumatic", and "leather".…”
Section: Sulfur Compoundsmentioning
confidence: 99%
“…At the same time, it was recognized that a substantial proportion of moderately smoke-exposed grape samples, especially from white varieties, will not inevitably give tainted wine. 11 While it has been shown that the concentrations of smoke-related phenols and glycosides in grapes can be used to predict "smoke" flavor intensity in wine, 11 it remains challenging to differentiate between smokeexposed grapes that may just yield recognizable but acceptable "smoky" characters and grapes that will, with a known degree of certainty, result in "smoke-tainted" wine that is unfit for sale. Hence, this perspective explores which concentrations of aroma compounds might lead to distinctive "smoky" characters versus those which could contribute to unacceptable smoke taint in wine.…”
Section: ■ Introductionmentioning
confidence: 99%